THE EFFECT OF HYDROTHERAPY EDUCATION SALT WATER SOAK IN IMPROVING THE COMFORT OF SCABIES SUFFERERS WITH ADOLESCENT KNOWLEDGE IN BOARDING SCHOOL DAR EL HIKMAH PEKANBARU - Citra Dewi Anitasari; Fatma Fatma Dewi; Rini Hariani Ratih (Jurnal Ilmu Kesehatan Abdurrab, 2025)
Background: Scabies is an infectious skin disease that is common in densely populated environments such as boarding schools. Low knowledge about personal hygiene and lack of information about alternative treatment methods cause a high incidence of scabies. Salt water hydrotherapy is one of the non-pharmacological methods that has the potential to improve the comfort of people with scabies. Objective: Knowing the effect of salt water hydrotherapy education on improving the comfort of scabies sufferers through increasing the knowledge of adolescents at Pondok Pesantren Dar El Hikmah Pekanbaru. Method: This study used a quantitative design with a one group pretest- posttest approach. The sample amounted to 155 respondents who were taken using total sampling technique. Data collection was done using questionnaires before and after education. Data analysis using Wilcoxon test. Results: Before education, 45.8% of respondents had poor knowledge. After education, 100% of respondents showed an increase in good knowledge. The results of the Wilcoxon test showed a p value = 0.000, which means that there is a significant effect of education on increasing adolescents' knowledge about salt water soak hydrotherapy. Conclusion: Education about salt water hydrotherapy has a significant effect in increasing adolescents' knowledge and comfort of scabies sufferers. This method is effective as an alternative health education in the boarding school environment and it is hoped that further research can carry out sustainable salt water soak hydrotherapy interventions through non-pharmacology or complementary approaches that are inexpensive and easy to make for all groups.